2021
DOI: 10.1186/s12880-021-00616-1
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of ultrasonography and Tc-99m MIBI SPECT/CT in preoperative localization of parathyroid adenomas causing primary hyperthyroidism

Abstract: Background Primary hyperparathyroidism (PHPT) results from an excess of parathyroid hormone (PTH) produced from an overactive parathyroid gland. The study aimed to explore the sonographic features of parathyroid adenomas and assess the diagnostic performance of ultrasonography (US) and Tc-99m MIBI SPECT/CT for preoperative localization of parathyroid adenomas. Methods A total of 107 patients were enrolled in this retrospective study who had PHPT an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…SPECT/CT demonstrated 93% sensitivity, 4D-CT 93% sensitivity, and ultrasonography 73% sensitivity. These numbers are in concordance with the results of the two meta-analyses [1,15] and with the later studies [18][19][20]. On the other hand, our sample size is too small for further subgroup analyses.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…SPECT/CT demonstrated 93% sensitivity, 4D-CT 93% sensitivity, and ultrasonography 73% sensitivity. These numbers are in concordance with the results of the two meta-analyses [1,15] and with the later studies [18][19][20]. On the other hand, our sample size is too small for further subgroup analyses.…”
Section: Discussionsupporting
confidence: 92%
“…We show an ectopic adenoma in Figure 3, and a syndromic (MEN) hypercalcemia patient in Figure 2. In a recent study consisting of 107 patients, SPECT was superior to US to detect ectopic disease, even though they found US superior to SPECT in detecting adenomas preoperatively [20]. Anecdotally, studies have shown that larger parathyroid adenomas are associated with lower vitamin D levels, which are more likely to be detected by 99m Tc-MIBI-SPECT/CT [23].…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity and specificity of ultrasonography is estimated to be 69-90% and 90-98%, respectively. For MIBI, similarly wide ranges have been reported (68-95%) [5]. The combination of both methods shows better performance (sensitivity and specificity 90-100%), while the highest diagnostic accuracy (97%) was achieved using the parathormone (PTH) concentration measurement in the washout from the ultrasound-guided biopsy (PTHw) of the suspected lesion [6].…”
Section: Introductionmentioning
confidence: 73%
“…USG has historically had favorable specificity and accuracy in adenoma detection, with published rates up to 93% and 88%, respectively. 21 It poses no radiation risk, and is lower cost compared to SES and 4D CT (which can be up to 6 times the cost of USG). 22,23 However, it is limited by patient body habitus, skill of the ultrasonographer, and concomitant thyroid disease.…”
Section: Discussionmentioning
confidence: 99%